New evidence of Early Cretaceous petrified wood in Yumen, north-western Gansu, China and its palaeogeographical implication. (3rd April 2021) - Yang, Guolin; Feng, Beizhan; Zheng, Fengjun; Ren, Wenxiu; Wang, Jun; Peng, Cuo; Deng, Peng; Guo, Bing; Tuo, Shibo
ABSTRACT: The phenomenon characterised by faster growth of the side of trees exposed to sunlight relative to the opposite side is termed plant phototropism. Vertical trunks of silicified wood occur in situ in the Hongliuxia area of Yumen City in north-western Gansu Province, China. A few trunks in the area exhibit well-preserved growth rings. Two petrified stumps reveal positive phototropism values of 279°–293° in the northwest direction. Living plants in Yumen City, Lanzhou City of Gansu Province and Beijing City showed positive phototropism values of 210°–255°±5° in the south-west direction. The evidence from wood phototropism supports clockwise rotation of the North China Block from previous palaeomagnetic studies since the Early Cretaceous. The petrified wood stumps in the Hongliuxia area of Yumen City are associated with 109 Ma strata corresponding to the main stage of the Yanshanian movement.